Scientific basis for design low-speed synchronous permanent magnet generators for wind power plants - A. A. Tatevosyan (Омский научный вестник)
In this paper, the scientific basis for designing wind power plants (WPP) with low-speed synchronous generators on permanent magnets (SGPM) is understood as a system of scientific knowledge that forms the theoretical basis for the practice of designing a complex object, such as WPP consisting of interconnected equipment and structures designed to convert wind energy into electrical energy. Currently, the development of advanced WPP designs is receiving increased attention around the world. For example, in the Russian Federation, a promising direction is the creation of Autonomous WPP with low-speed medium- and low- power SGPMs that have the maximum range of applications by type of activity and climate zones throughout the territory. However, engineering approaches to the design of individual components of the WPP indicate the difficulties of developing a scientifically based methodology for optimizing the parameters of the WPP as a whole taking into account the mutual influence of individual components on each other. At the same time, the methodology for optimizing the parameters of WPP is understood as a tool for the scientific basis of design, which takes into account quality indicators and optimality criteria, energy and technical characteristics, as well as design stages with the results of preliminary and verification calculations. For the stage of verification calculations of VEU parameters, the scientific basis of design is determined by the construction of mathematical models and their research using application software packages for PCs, while for the stage of preliminary calculations, the development of analytical methods of analysis is important. This article discusses the scientific basis for designing wind turbines at the stage of preliminary calculations, formulated the problem of optimizing the parameters of low-speed WPP, proposed equations for the relationship of design parameters with the energy performance of wind turbines, providing the maximum efficiency of synchronous generators, taking into account the specified technical conditions.